A numerical protocol for death-time estimation - Mfolozi, Sipho (Department of Clinical Laboratory Sciences, 2022)
A body's axial temperature distribution at death was experimentally demonstrated by the author to predict the postmortem temperature plateau (PMTP), which is known to affect the measured core temperature value and hence death-time estimation. Yet today's methods of death-time estimation apply only a single-point approximation of a body's core temperature in life as well as a single-point measurement of a body's core temperature after death. Four studies were carried out to understand the relationship between a body's axial temperature distribution and the PMTP. The first study numerically approximated antemortem temperature distribution in an MRI-built, high-definition, anatomicallys egmented 3D computational human phantom consisting of several hundred tissues.